Relationship between Corporate Governance Dimensions and Financial Performance of Listed Insurance Companies in Muscat Securities Market, Sultanate of Oman (International Journal of Scientific Research and Management (IJSRM), 2022)
This study aims at determining the factors of corporate governance that impact financial performance. It uses a panel analysis approach that considers data from 2004 to 2018 of the insurance companies in Muscat, Oman. Out of the 10 insurance companies listed in Muscat Securities Market, four companies were chosen based on pre-established criteria considering the availability of data for the period indicated. To analyze the data gathered, descriptive analysis techniques using SPSS version 21 and Stata version 14 were applied. Based on the findings, board size affects ROA positively but negatively on ROE; FBM affects ROE positively but negatively affects ROA; BI has a negative influence on both ROA and ROE; and, AC affects ROA positively but negatively on ROE. Conversely, audit committee size positively impacts ROA and the independence and impartiality is a must to be a member of the audit committee. Conclusion from the findings suggests that the increasing number of the members of audit committee contributes positive signs for ROA which can be supported by many studies. Findings proved the significant positive relationship between audit committee size and independence on a firm’s financial performance. For organizations such as insurance companies, the frequency of board meetings can be determining factor to decide in terms of profitability issues and business performance. Finally, the results provide the management to examine the implications of deciding how many members of the board, frequency of board meetings, board independence, and audit committee as these can influence financial performance such as ROA and ROE.